Hydrogenation behavior of Cr-coated laser beam welds of E110 zirconium alloy; Journal of Nuclear Materials; Vol. 570 - Kashkarov E. B. Egor Borisovich; Kudiyarov V. N. Victor Nikolaevich; Kurdyumov N. Nikita; Krinitsyn M. G. Maksim Germanovich; Sidelev D. V. Dmitry Vladimirovich (2022, 2022)
Title screen